DOI: 10.1007/978-0-387-78885-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation with Ser/Thr Kinase Cascade and a His/Asp TCS in Myxococcus xanthus

Abstract: Fruiting body development of Myxococcus xanthus is propelled by temporal gene expression directed via stage-specific intercellular signaling pathways. M. xanthus exhibits social behaviors during its complex life cycle and is a potential source for production of natural products such as secondary metabolites. The numerous signaling pathways of M. xanthus consist of not only the two-component His-Asp phosphorelay system (TCS) but also protein Ser/Thr kinases (PSTKs) that regulate gene expression, motility and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…If unfavorable conditions persist, the aggregated cells can form metabolically dormant myxospores until nutrients become available again. The tight regulation of this complex developmental cycle has been reviewed in detail (69). Briefly, FruA is a key transcription factor that regulates the expression of a large number of genes involved in both fruiting body formation and sporulation.…”
Section: Estks In Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…If unfavorable conditions persist, the aggregated cells can form metabolically dormant myxospores until nutrients become available again. The tight regulation of this complex developmental cycle has been reviewed in detail (69). Briefly, FruA is a key transcription factor that regulates the expression of a large number of genes involved in both fruiting body formation and sporulation.…”
Section: Estks In Bacteriamentioning
confidence: 99%
“…The eSTK Pkn14 also regulates MrpC by phosphorylating it on a Thr residue(s), reducing its affinity for both its own promoter and the fruA promoter (119,120). The transmembrane eSTK Pkn8 phosphorylates Pkn14, and it has been suggested that Pkn8 and -14 form an eSTK cascade that inhibits the activity of MrpC during vegetative growth (69,119) (Fig. 5).…”
Section: Estks In Bacteriamentioning
confidence: 99%
“…The eSTKs have been widely studied for their roles in diverse biological processes, including development (Zhang, 1993; Nádvorník et al, 1999; Inouye and Nariya, 2008), cell competence (Hussain et al, 2006), cell division, and cell wall synthesis (Deol et al, 2005; Fernandez et al, 2006; Ruggiero et al, 2012), central and secondary metabolism (Lee et al, 2002; Sawai et al, 2004), biofilm formation (Hussain et al, 2006; Liu et al, 2011), stress response (Neu et al, 2002; Mata-Cabana et al, 2012), and virulence (Madec et al, 2002; Rajagopal et al, 2003; Echenique et al, 2004). Gene expression profiles have proven their global regulatory roles in cellular processes (Sasková et al, 2007; Donat et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For a discussion of FruA's roles in aggregation and in the C-signaling network, see previous reviews in references 24,88,89, and 32; they will not be discussed in detail here. The results of several studies indicate that FruA plays a direct role in the regulation of sporulation.…”
Section: Late Regulators Of Sporulationmentioning
confidence: 99%